Estimation of hair cortisol levels as a biomarker of chronic stress in psoriasis: A pilot study - Leelavathy Budamakuntla; Eswari Loganathan; Heera Ramesh; Priyanka Karagaiah; Sachin Somashekhar; Shankar Kumar Venkatarayaraju (Wolters Kluwer Medknow Publications, 2023)
Background: Psychological stress can exacerbate many inflammatory diseases like psoriasis by dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. One method of establishing this correlation is by measuring cortisol levels. Deposition of cortisol in the hair during its growth allows for retrospective quantification and to analyze the relationship between hair cortisol levels, stress, and psoriasis. Objective: The objective of this study is to evaluate hair cortisol levels as a biomarker of chronic stress in psoriasis patients. Materials and Methods: Detailed clinical and personal history and stress-related events before the onset of the disease or any exacerbations during the disease were taken. Clinical severity was assessed using psoriasis area and severity index (PASI) scoring. Stress levels in individuals, during the previous 6 months were assessed, using Holmes-Rahe Life Stress Inventory. Following this, hair samples were collected from the vertex of the scalp and sent to the laboratory in an envelope. After extraction of the cortisol, their levels were estimated using an enzyme-linked immunosorbent assay. Statistical analyses were done. Results: Mean hair cortisol level per mg of hair sample was 0.92 ± 0.84 ng/mg compared to 0.50 ± 0.60 ng/mg in controls (P = 0.002). There was a significant positive correlation of hair cortisol levels with the duration of disease, PASI score, and stress level. Conclusion: Measurement of cortisol in hair is a novel, noninvasive method that may assess systemic cortisol levels over several weeks to months. It may potentially be used as a biomarker in psychocutaneous disorders like psoriasis.